Experimental Analysis of Oscillatory Vortex Generators in Wind Turbine Blade - Hector G. Parra; Hernan D. Ceron; William Gomez; Elvis E. Gaona (Energies, 2023)
Vortex generators are devices that modify the wind behavior near the surface of wind turbine blades. Their use allows the boundary layer shedding transition zone to be varied. Bio-inspired design has been used to improve the efficiency of aerodynamic and hydrodynamic systems by creating devices that use shapes present in animals and plants. In this work, an experimental methodology is proposed to study the effect of bio-inspired vortex generators and their effect on the structural vibration of a blade. In addition, the wind wake generated by the blade with oscillating vortex generators at different oscillation frequencies is analyzed by means of a hot wire anemometer, obtaining appreciable vibration reduction results in the measured 3D acceleration signals for wind velocities between 10 and 15 m/s. Values of the spectral components of the wake velocity measured at higher tunnel wind velocities increase. Spectral variance is reduced at higher tunnel wind velocities. The system analyzed in this paper can contribute in the future to the construction of actuators for vibration compensation systems in wind turbines.